Electric field bridging-effect in electrified microfibrils’ scaffolds - Fontana, Sara; Caramazza, Laura; Marracino, Paolo; Cuenca Ortolá, Irene; Colella, Micol; Dolciotti, Noemi; Paffi, Alessandra; Gisbert Roca, Fernando; Ivashchenko, Sergiy; Más Estellés, Jorge; Consales, Claudia; Balucani, Marco; et al. (Frontiers in Bioengineering and Biotechnology, 2023)
Introduction: The use of biocompatible scaffolds combined with the implantation of neural stem cells, is increasingly being investigated to promote the regeneration of damaged neural tissue, for instance, after a Spinal Cord Injury (SCI). In particular, aligned Polylactic Acid (PLA) microfibrils’ scaffolds are capable of supporting cells, promoting their survival and guiding their differentiation in neural lineage to repair the lesion. Despite its biocompatible nature, PLA is an electrically insulating material and thus it could be detrimental for increasingly common scaffolds’ electric functionalization, aimed at accelerating the cellular processes. In this context, the European RISEUP project aims to combine high intense microseconds pulses and DC stimulation with neurogenesis, supported by a PLA microfibrils’ scaffold. Methods: In this paper a numerical study on the effect of microfibrils’ scaffolds on the E-field distribution, in planar interdigitated electrodes, is presented. Realistic microfibrils’ 3D CAD models have been built to carry out a numerical dosimetry study, through Comsol Multiphysics software. Results: Under a voltage of 10 V, microfibrils redistribute the E-field values focalizing the field streamlines in the spaces between the fibers, allowing the field to pass and reach maximum values up to 100 kV/m and values comparable with the bare electrodes’ device (without fibers). Discussion: Globally the median E-field inside the scaffolded electrodes is the 90% of the nominal field, allowing an adequate cells’ exposure.